The PRESCRIPTIVE ON THE IMPACT OF FINANCIAL DEVELOPMENT AND EXPORTS IN INDONESIA - Faiza, Laila Niswatul; Wardhono, Adhitya; Yuliati, Lilis (Jurnal Ekuilibrium, 2024)
Export activities contribute to economic development so it is necessary to make various efforts to increase exports in a country. Exports are influenced by factors that become a country's comparative advantage in conducting international trade. The superior factor discussed in this journal is the development of the financial sector. An advanced financial sector can reduce industrial exporters' barriers to exporting, especially barriers to funding and shipping. This research aims to look at the impact of financial development on exports in Indonesia. This research uses descriptive analysis methods. The results of the descriptive analysis show that the increase in financial development is not accompanied by an increase in exports in Indonesia which is due to a lack of channeling funds to the exporter sector and there are obstacles to carrying out export activities.